- #1

- 160

- 0

So I applied the product rule

(f • g) = x • e(^2x) + e^(2x) • 1

= xe^(2x) + e^(2x)

=2xe^(2x)

And got this as my final answer.

Would I need to use chain rule? Did I do this correctly?

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter CrossFit415
- Start date

- #1

- 160

- 0

So I applied the product rule

(f • g) = x • e(^2x) + e^(2x) • 1

= xe^(2x) + e^(2x)

=2xe^(2x)

And got this as my final answer.

Would I need to use chain rule? Did I do this correctly?

- #2

- 186

- 1

You forgot to take the derivative of e^(2x)f(x)= xe^(2x)

(f • g)' = x • e(^2x) + e^(2x) • 1

Share: